Sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite cathode material and its preparation and application

Through the two-stage roasting process and waste recycling technology of sodium ferrous phosphate-graphitized carbon @ amorphous carbon composite material, the problem of poor electrochemical performance of sodium ion battery positive electrode material is solved, and high-performance and low-cost material preparation is achieved , improves the cycle stability and capacity of sodium ion batteries.

CN115275125BActive Publication Date: 2025-01-03HUNAN NABANG NEW ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202110483076.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-04-30
Publication Date
2025-01-03
Estimated Expiration
2041-04-30

AI Technical Summary

Technical Problem

The electrochemical performance of the cathode material of sodium ion battery is poor, especially the circulation performance is poor at high magnifications, and the existing preparation methods are costly and the material morphology is not ideal.

Method used

Using sodium ferrous phosphate-graphitized carbon @ amorphous carbon composite material, the crystal phase structure and ion conduction network are controlled through the two-stage roasting process, combined with waste recycling technology to reduce costs.

Benefits of technology

It significantly improves the capacity, magnification and cycle stability of sodium ion batteries, realizes high performance and low cost preparation of materials, and solves the problem of waste recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003049170290000011
    Figure HDA0003049170290000011
  • Figure HDA0003049170290000012
    Figure HDA0003049170290000012
  • Figure HDA0003049170290000021
    Figure HDA0003049170290000021
Patent Text Reader

Abstract

The present invention belongs to the technical field of sodium ion batteries, and specifically discloses a sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material, which includes a core and an amorphous carbon coated on the surface of the core; the core is a composite of graphitized carbon and sodium ferrous fluorophosphate. The preparation method of the material is: ferric phosphate, graphitized carbon and a surfactant are dispersed in liquid phase, followed by solid-liquid separation, drying, and a first-stage roasting treatment to obtain an iron phosphate@graphitized carbon precursor; the iron phosphate@graphitized carbon precursor, an amorphous carbon source, a sodium source, and a fluorine source are roasted in a second stage to obtain a sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material. The material described in the present invention has good electrochemical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention belongs to the technical field of battery materials, and in particular relates to the technical field of positive electrode active materials for sodium ion batteries. Background technology:

[0002] With the successful application of lithium-ion batteries around the world, people's demand for large-scale energy storage systems and environmentally friendly vehicles is increasing, and the consumption of lithium resources is quite significant. However, the reserves of lithium in the earth's crust are limited and unevenly distributed. The shortage of lithium resources is an important factor restricting its development. Sodium and lithium belong to the same main group and have certain similar physical and chemical properties, but the radius of sodium is larger than that of lithium. Many materials and material construction theories suitable for lithium-ion batteries are difficult to apply in the field of sodium-ion batteries, and it is difficult to obtain technical effects similar to those of lithium-ion batteries. This is the main reason why lithium-ion batteries have been widely used while sodium-ion batteries have not been widely commercialized.

[0003] The research on positive electrode materials for Na-ion batteries has evolved from layered oxide positive electrode materials to tunnel structure oxide materials. The final direction has shifted to the research of olivine structured polyanion positive electrode materials. These compounds have high thermal stability due to the strong covalent bonds of oxygen atoms in the polyanion polyhedrons, and because they have multidimensional ion migration channels, they have good ion embedding / de-embedding stability, making them suitable choices for Na-ion battery positive electrode materials.

[0004] Fluorophosphoric acid system transition metal materials have a lattice structure different from the phosphoric acid system, providing a two-dimensional channel for ion conduction, which is conducive to the improvement of discharge stability and capacity. Na2FePO4F has a high theoretical capacity (135mAh·g -1 ) and a stable charge and discharge platform (3.0V), and a stable structure, making it a promising sodium-ion battery cathode material.

[0005] Nazar et al. first proposed the Na2FePO4F material, which is considered to be 3.5V (vs.Li + / Li) lithium-sodium hybrid battery positive electrode material can achieve a Na + Its skeleton structure shows unique characteristics. The dioctahedral [Fe2O7F2] unit is composed of coplanar FeO4F2 regular octahedrons, which are connected into chains by F atoms and connected with PO4 tetrahedrons to form layers, and have two-dimensional ion channels that are easy to diffuse. + The ion deintercalation process exhibits a smooth slope behavior (about 0.6Na) with a potential platform at 3.0V and a unit cell volume change rate of 3.7%. However, the cycling performance of this material at high rates is poor and requires further research.

[0006] At present, there are many different preparation methods that can be used to synthesize Na2FePO4F materials, mainly including solid phase method, sol-gel method, carbon thermal reduction method, etc. For example, usually sodium source, iron source, phosphorus source, and fluorine source are mixed and sintered. The crystal phase structure and morphology uniformity of the material obtained by this method are not ideal, and the electrochemical performance of the obtained material needs to be improved. In addition, the cost of its synthesis is high. Summary of the invention:

[0007] In view of the problems of the prior art, the first purpose of the present invention is to provide a sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material (the present invention is also called sodium ferrous fluorophosphate-C@C composite material), aiming to obtain a new material with a dual-carbon structure that is conducive to sodium ion deintercalation and improves the electrochemical performance of sodium ion batteries.

[0008] The second object of the present invention is to provide a method for preparing a sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material, and in particular to a method for preparing the material using materials recycled from waste.

[0009] The third object of the present invention is to provide a sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material for use in sodium ion batteries.

[0010] A sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material comprises a core and amorphous carbon coated on the surface of the core; the core is a composite of graphitized carbon and sodium ferrous fluorophosphate.

[0011] The present invention provides a sodium ferrous fluorophosphate composite material with a dual-carbon structure, in which sodium ferrous fluorophosphate is pre-compounded with graphitized carbon and then coated with amorphous carbon. Studies have found that the material with this structure can effectively improve the Na embedding and de-embedding of the material, improve the Na ion and electron conduction network, and help improve the capacity, rate and cycle stability of the material.

[0012] In the present invention, the graphitized carbon is at least one of one-dimensional carbon, two-dimensional carbon, and three-dimensional carbon;

[0013] Preferably, the graphitized carbon is at least one of graphene, carbon nanotubes, and carbon nanofibers;

[0014] Preferably, the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material is nanoparticles.

[0015] Preferably, the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material is radial or flaky, and the particle size is 200 to 500 nm.

[0016] The present invention also provides a method for preparing the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material, comprising the following steps:

[0017] Step (1):

[0018] The iron phosphate, graphitized carbon and surfactant are dispersed in liquid phase, and then solid-liquid separation, drying and first-stage calcination are performed to obtain an iron phosphate@graphitized carbon precursor;

[0019] Step (2):

[0020] The iron phosphate@graphitized carbon precursor, the amorphous carbon source, the sodium source and the fluorine source are subjected to a second stage of calcination to obtain a sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material.

[0021] Different from the conventional solid phase and sol-gel preparation methods, the technical solution of the present invention pre-loads iron and phosphorus in the form of iron phosphate on the graphitized carbon structure, and then participates in the subsequent sodiumization and fluorination calcination. In this way, the crystal phase structure of sodium ferrous fluorophosphate can be controlled, the unit cell size can be controlled, the material morphology can be improved, and the ion and electron conduction network can be effectively constructed, thereby effectively improving the capacity, rate, and cycle stability of the material.

[0022] The present invention has found that the iron-phosphorus is pre-loaded on the graphitized carbon network in the form of iron phosphate phase, which is the key to improving the subsequent sodium-fluorination reaction effect, improving the material properties, and improving the electrochemical performance. In the present invention, the iron phosphate phase is combined with the two-stage carbon matching process to synergistically improve the material phase and morphology, and improve the electrochemical performance of the material.

[0023] In the present invention, the ferric phosphate is obtained by pre-reacting a trivalent iron source and a phosphate source;

[0024] Preferably, the iron source is Fe 3+ The water-soluble salt is preferably at least one of ferric chloride, ferric sulfate, ferric nitrate, ferric acetate and ferric citrate;

[0025] The phosphorus source is PO4 3- The water-soluble acid or salt is preferably at least one of phosphoric acid, sodium dihydrogen phosphate, ammonium dihydrogen phosphate, disodium hydrogen phosphate, and diammonium hydrogen phosphate.

[0026] The iron source and phosphorus source are mixed according to a stoichiometric ratio.

[0027] In another embodiment of the same inventive concept of the present invention, the iron phosphate is obtained by a recycling process of phosphorus-iron waste. The present invention has found that the iron phosphate obtained by recycling waste can obtain a material with good electrochemical properties based on the treatment method of the present invention. More importantly, it can solve the problem of waste recycling, realize high-value conversion of waste, and effectively reduce the processing cost.

[0028] Preferably, the iron phosphate is recovered from waste lithium iron phosphate electrode materials;

[0029] The preferred recovery process is:

[0030] The waste lithium iron phosphate electrode material is placed in a strong acid oxidation solution for treatment, and then solid-liquid separation and drying are performed to obtain;

[0031] The strong acid oxidation solution is a solution mixed with a strong acid, an oxidant and ferrous ions;

[0032] The strong acid is at least one of hydrochloric acid, sulfuric acid and nitric acid;

[0033] The oxidant is at least one of hydrogen peroxide, potassium permanganate and sodium peroxide;

[0034] Preferably, the molar volume ratio of the strong acid:oxidant:ferrous ion is (1.05-1.25):(2-4):1;

[0035] Preferably, the temperature of the treatment process is 25 to 50°C;

[0036] Preferably, the treatment process lasts for 15 to 120 minutes.

[0037] The present invention, in addition to innovatively converting iron and phosphorus into an iron phosphate intermediate phase in advance to participate in the subsequent sodium-fluorination calcination, further pre-calcines the iron phosphate and loads it in a graphitized carbon structure network, which helps to further improve the structure and electrochemical properties of the prepared material.

[0038] In the present invention, the surfactant is an anionic surfactant.

[0039] Preferably, the surfactant is at least one of sodium dodecylbenzene sulfonate and sodium α-olefin sulfonate.

[0040] In the present invention, the graphitized carbon is a single carbon substance, for example, at least one of one-dimensional carbon, two-dimensional carbon, and three-dimensional carbon; more preferably, the graphitized carbon is at least one of graphene, carbon nanotubes, and carbon nanofibers.

[0041] Preferably, the mass ratio of iron phosphate, graphitized carbon and surfactant is (90-100):(7-10):1.

[0042] In the present invention, iron phosphate, graphitized carbon and surfactant are mixed in liquid phase, for example, each component is mixed in liquid phase with water, and the liquid phase mixing time is, for example, 6 to 24 hours; then solid-liquid separation, water washing, drying, post-grinding, and then the first stage of roasting are carried out.

[0043] In the present invention, the first stage calcination is carried out under a protective atmosphere.

[0044] Preferably, the protective atmosphere is nitrogen or an inert gas, such as argon.

[0045] Preferably, the temperature of the first calcination process is 300-400°C; more preferably, 350-400°C.

[0046] Preferably, the first calcination period is 3 to 5 hours.

[0047] In the present invention, the iron phosphate phase is innovatively loaded on a graphitized carbon element, and then compounded with a sodium source, a fluorine source and an amorphous carbon source (preferably by liquid phase ball milling) to obtain a mixture, followed by a second stage of roasting.

[0048] Preferably, in step (2), the components are compounded into a mixed material by liquid phase ball milling.

[0049] In the liquid phase ball milling, the solvent is at least one of distilled water, anhydrous ethanol, acetone and isopropanol;

[0050] The rotation speed of the wet ball milling is 400-800 rpm, and the ball milling time is 8-16 hours.

[0051] The amorphous carbon source is at least one of glucose, ascorbic acid, sucrose, etc.;

[0052] Preferably, the sodium source is a component capable of providing the Na element, preferably at least one of sodium carbonate, sodium bicarbonate, sodium acetate, sodium dihydrogen phosphate and disodium hydrogen phosphate;

[0053] Preferably, the fluorine source is a component capable of providing a fluorine source, preferably at least one of sodium fluoride, ammonium fluoride, and hydrogen fluoride;

[0054] Preferably, the iron phosphate@graphitized carbon precursor, the sodium source, and the fluorine source are mixed in a molar ratio of iron phosphate:F:Na of 1-1.2:1-1.3:1-1.1;

[0055] Preferably, the mass ratio of the amorphous carbon source to the iron phosphate@graphitized carbon precursor is 3-10 wt.%, and more preferably 6-10 wt.%.

[0056] The second stage of calcination is carried out under a protective atmosphere;

[0057] Preferably, the protective atmosphere is nitrogen or an inert gas;

[0058] Preferably, the temperature of the second calcination process is 600-650°C;

[0059] Preferably, the second calcination time is 6 to 10 hours.

[0060] The technical solution of the present invention can preferably use waste materials for material preparation, and the steps are as follows:

[0061] (1) preparing a strong acid oxidizing solution having a molar volume ratio of strong acid: oxidant: ferrous ion of (1.05-1.25):(2-4):1;

[0062] (2) adding lithium iron phosphate waste to a strong acid oxidation solution at a liquid-to-solid ratio of (2-4):1, heating to 25-50°C while stirring, reacting for 15-120 minutes, and then separating the iron phosphate material;

[0063] (3) adding the iron phosphate material as a raw material into a certain amount of deionized water; adding a certain proportion of carbon-based material and surfactant, and stirring thoroughly overnight to obtain carbon-coated iron phosphate;

[0064] (4) filtering the composite material obtained in step (3) with a detergent or suction filtration and placing it in an oven at a temperature of 80 to 120° C., grinding it thoroughly and placing it in a quartz crucible, calcining it at 300 to 400° C. under nitrogen or argon protection, and keeping it warm for 3 to 5 hours to obtain an iron phosphate carbon-coated precursor with a size of 200 nm to 500 nm;

[0065] (4) The powder obtained in step (4) is added with glucose at a ratio of 3% to 8% of the mass of the final product accounted for by carbon, and then placed in a ball mill according to the molar ratio of FePO4:F:Na=1-1.2:1-1.3:1-1.1 in iron phosphate:fluorine source:sodium source, and then fully ground by wet ball milling. Then, the powder is placed in a quartz crucible, and calcined at 600-650° C. under nitrogen or argon protection, and kept warm for 6-10 hours to obtain carbon-coated sodium ferrous fluorophosphate with a size of 200nm-500nm.

[0066] The present invention recovers industrialized iron phosphate from waste lithium iron phosphate as a precursor, first mixes it with a carbon-based material, and then adopts a wet ball milling method to mix it with a fluorine source and a sodium source to obtain a sodium ferrous fluorophosphate composite material. The present invention can obtain uniform carbon source-coated sodium ferrous fluorophosphate, and the obtained carbon-coated sodium ferrous fluorophosphate powder has low cost, large output, environmental friendliness, uniform carbon source coating, uniform particle morphology, uniform particle size distribution, ideal crystal structure, and good industrial application prospects.

[0067] The present invention also provides an application of the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material for preparing a sodium ion battery; preferably, it is used as a positive electrode active material for preparing a positive electrode of a sodium ion battery.

[0068] The present invention also provides a sodium ion battery, which comprises the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material; preferably, the positive electrode in the sodium ion battery contains the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material.

[0069] The present invention has the following notable features:

[0070] (1) The present invention provides a sodium ferrous fluorophosphate with a dual-carbon structure, which, thanks to the control of the dual-carbon composite structure of the material, can effectively improve the capacity, rate and cycle stability of the material.

[0071] (2) The present invention also provides a method for preparing the dual-carbon structure material, which innovatively loads iron-phosphorus in the form of iron phosphate on graphitized carbon and then participates in a subsequent sodium-fluorination roasting treatment. This helps to improve the material's phase, crystal structure, and morphology, and helps to improve the material's electrochemical properties.

[0072] (3) The present invention can obtain iron phosphate by recycling waste materials, and then load it on graphitized carbon, and participate in subsequent sodium-fluoride roasting. This can realize the utilization of waste materials, reduce costs, and help obtain materials with good performance.

[0073] For example, a preferred solution of the present invention is to use waste lithium iron phosphate in the lithium-ion battery system to recover iron phosphate as a raw material to prepare sodium ferrous fluorophosphate, which can not only recycle lithium iron phosphate batteries in large quantities to avoid waste of resources, but also can prepare industrial iron phosphate at low cost and high output.

[0074] This method is low-cost, high-yield, environmentally friendly, simple to operate, mild conditions, and highly controllable, and has good prospects for industrial application. Description of the drawings:

[0075] Figure 1 is the X-ray diffraction pattern of FePO4;

[0076] Figure 2 is the X-ray diffraction pattern of Na2FePO4F;

[0077] Figure 3 SEM image of Na2FePO4F

[0078] Figure 4 The cycle performance diagram of the material prepared in Example 1

[0079] Figure 5 The cycle performance diagram of the material prepared in Example 2

[0080] Figure 6 The cycle performance diagram of the material obtained in Example 3

[0081] Figure 7 The cycle performance diagram of the material obtained in Example 4

[0082] Figure 8 The cycle performance diagram of the material obtained in Example 5

[0083] Fig. 9 The cycle performance diagram of the material obtained in Example 6

[0084] Fig.10 The cycle performance diagram of the material obtained in Example 7

[0085] Fig.11 The cycle performance diagram of the material prepared in Comparative Example 1

[0086] Fig.12 Cyclic performance diagram of the material obtained in Comparative Example 2

[0087] Fig.13 The cycle performance diagram of the material obtained in Comparative Example 3

[0088] Fig.14 The cycle performance diagram of the material obtained in Comparative Example 4

[0089] Fig.15 The cycle performance diagram of the material obtained in Comparative Example 5

[0090] Fig.16 The cycle performance diagram of the material prepared in Comparative Example 6 Specific implementation method:

[0091] Example 1

[0092] (1) preparing a strong acid oxidizing solution, wherein the molar volume ratio of strong acid: oxidant: ferrous ion is 1:2:1, the strong acid is sulfuric acid, and the oxidant is hydrogen peroxide;

[0093] (2) adding lithium iron phosphate waste to a strong acid oxidation solution at a liquid-to-solid ratio of 3:1, heating to 50° C. while stirring, reacting for 30 minutes, and then separating the iron phosphate material;

[0094] (3) The iron phosphate material was dissolved in deionized water, 8 wt.% of graphene (based on the weight of iron phosphate) and 1 wt.% of sodium dodecylbenzene sulfonate (based on the weight of iron phosphate) were added, the rotation speed was adjusted to 600 rpm and stirred overnight, and then the mixture was placed in a 100°C oven after being filtered with water. After being fully ground, the mixture was sintered at 350°C in an argon atmosphere (first sintering) for 4 h to obtain a graphene-iron phosphate composite material.

[0095] (4) The graphene-iron phosphate composite material of step (3) (calculated by molar iron phosphate) is added with sodium acetate, sodium fluoride in a ratio of iron phosphate: Na: F of 1:1.1:1.1 and 8 wt.% of glucose (based on the graphene-iron phosphate composite material) into a ball mill, and an ethanol solvent is added. The rotation speed is adjusted to 500 rpm. After ball milling for 8 hours, it is dried and sintered at 650° C. in an argon atmosphere (second stage sintering) for 8 hours to obtain a high-performance dual-carbon structure sodium ferrous fluorophosphate composite material.

[0096] Example 2

[0097] Compared with Example 1, the only difference is the source of iron phosphate, analytically pure iron phosphate is used as the raw material, and the other steps are the same.

[0098] Example 3

[0099] Compared with Example 1, the only difference is that the graphitized carbon is changed from graphene to carbon nanotubes, and the other steps are the same.

[0100] Example 4

[0101] Compared with Example 1, the only difference is that the amorphous carbon is changed from glucose to ascorbic acid, and the other steps remain unchanged.

[0102] Example 5

[0103] Compared with Example 1, the difference is that the second stage calcination temperature is changed to 600° C., and the other steps remain unchanged.

[0104] Example 6

[0105] Compared with Example 1, the only difference is that the temperature of the first sintering process is 400° C., and the other steps remain unchanged.

[0106] Example 7

[0107] Compared with Example 1, the only difference is that in step (4), the amount of glucose added is 10 wt %, and the other steps remain unchanged.

[0108] Comparative Example 1

[0109] Compared with Example 1, the difference is that the precursor iron phosphate is not synthesized, and the iron source, phosphorus source, graphitized carbon, amorphous carbon source, sodium source, and fluorine source are directly mixed in corresponding proportions (the same as in Example 1), pre-sintered at 350°C for 4 hours in the first stage, and then second calcined at 650°C for 8 hours to directly obtain the sodium ferrous fluorophosphate composite material; the parameter conditions are the same as in Example 1.

[0110] Comparative Example 2

[0111] Compared with Example 1, the difference is that no graphitized carbon is added, and the iron phosphate is directly compounded with the sodium acetate, sodium fluoride, glucose, and sodium dodecylbenzene sulfonate in step (4) in liquid phase and then sintered (calcined at 650° C. for 8 h), and the other steps and parameters are the same.

[0112] Comparative Example 3

[0113] Compared with Example 1, the difference is that no amorphous carbon is added in the second stage of roasting, and the other steps are the same.

[0114] Comparative Example 4

[0115] Compared with Example 1, the difference is that the second stage calcination temperature is 500° C., and the other steps are the same.

[0116] Comparative Example 5:

[0117] Compared with Example 1, the only difference is that in step (3), an amorphous carbon source is used to replace the graphene (the amorphous carbon source is glucose, and its weight is 8wt% of the iron phosphate).

[0118] Comparative Example 6:

[0119] Compared with Example 1, the only difference is that in step (3), no surfactant is added.

[0120] The main steps of the test are:

[0121] (1) Using a 2032 model battery case, the positive electrode is a prepared sodium ferrous fluorophosphate electrode (the current collector is aluminum foil, active material: conductive carbon: PVDF = 7:2:1), the negative electrode is sodium metal, a fiber separator (model Whatman Grade GF / D), and the electrolyte is 1M NaClO4 (pure PC + 5% FEC) to assemble the battery;

[0122] (2) The rest time is 12 h, and a rate charging program is set, with a rate of 0.1C, a voltage range of 2.0 V-4.0 V, and 50 cycles;

[0123] (3) The theoretical specific capacity of sodium ferrous fluorophosphate is 124 mAh / g;

[0124] The test results are shown in Table 1:

[0125] First cycle capacity (mAh / g) Capacity after 50 cycles (mAh / g) Capacity retention rate (%) Example 1 112.7 106.3 94.3 Example 2 108.2 100.5 92.8 Example 3 109.5 103.3 94.3 Example 4 110.7 104.2 94.1 Example 5 97.5 91 93.3 Example 6 110.8 104.9 94.7 Example 7 113.6 109.2 96.1 Comparative Example 1 98.7 88.2 89.3 Comparative Example 2 87.5 77.1 88.1 Comparative Example 3 82.7 68.1 82.3 Comparative Example 4 74.7 60.1 80.4 Comparative Example 5 84.5 72.2 85.4 Comparative Example 6 85.1 73.3 86.1

[0126] Research has found that the use of the iron phosphate described in the present invention in combination with the dual carbon sintering process can effectively improve the electrochemical properties of the prepared material and can also achieve the utilization of waste materials.

Claims

1. A sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material, characterized in that: It includes a core and amorphous carbon coated on the surface of the core; the core is a composite of graphitized carbon and sodium ferrous fluorophosphate; The preparation of sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material includes the following steps: Step (1): The iron phosphate, graphitized carbon and surfactant are dispersed in liquid phase, and then solid-liquid separation, drying and first-stage calcination are performed to obtain an iron phosphate@graphitized carbon precursor; Step (2): The iron phosphate@graphitized carbon precursor, the amorphous carbon source, the sodium source and the fluorine source are subjected to a second stage of calcination to obtain a sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material.

2. The sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 1, characterized in that: The graphitized carbon is at least one of one-dimensional carbon, two-dimensional carbon and three-dimensional carbon.

3. The sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 1, characterized in that: The graphitized carbon is at least one of graphene, carbon nanotubes and carbon nanofibers.

4. The sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 1, characterized in that: The sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material is nanoparticles.

5. The sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 4, characterized in that: The particle size of the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material is 200-500nm.

6. The sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 1, characterized in that: The mass percentage of amorphous carbon and graphitized carbon is 2~10%.

7. A method for preparing the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step (1): The iron phosphate, graphitized carbon and surfactant are dispersed in liquid phase, and then solid-liquid separation, drying and first-stage calcination are performed to obtain an iron phosphate@graphitized carbon precursor; Step (2): The iron phosphate@graphitized carbon precursor, the amorphous carbon source, the sodium source and the fluorine source are subjected to a second stage of calcination to obtain a sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material.

8. The method for preparing the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 7, characterized in that: The ferric phosphate is obtained by pre-reacting a trivalent iron source and a phosphorus source.

9. The method for preparing the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 8, characterized in that: The iron source is Fe 3+ water-soluble salts.

10. The method for preparing the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 9, characterized in that: The iron source is at least one of ferric chloride, ferric sulfate, ferric nitrate, ferric acetate and ferric citrate.

11. The method for preparing the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 8, characterized in that: The phosphorus source is PO4 3- water-soluble acids or salts.

12. The method for preparing the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 11, characterized in that: The phosphorus source is at least one of phosphoric acid, sodium dihydrogen phosphate, ammonium dihydrogen phosphate, disodium hydrogen phosphate and diammonium hydrogen phosphate.

13. The method for preparing the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 7, characterized in that: The iron phosphate is obtained by recycling phosphorus-iron waste.

14. The method for preparing the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 7, characterized in that: The iron phosphate is recovered from waste lithium iron phosphate electrode materials.

15. The method for preparing the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 14, characterized in that: The recycling process of waste lithium iron phosphate electrode materials is: The waste lithium iron phosphate electrode material is placed in a strong acid oxidation solution for treatment, and then solid-liquid separation and drying are performed to obtain; The strong acid oxidation solution is a solution containing strong acid, oxidant and ferrous ions; The strong acid is at least one of hydrochloric acid, sulfuric acid and nitric acid; The oxidant is at least one of hydrogen peroxide, potassium permanganate and sodium peroxide; The molar volume ratio of the strong acid:oxidant:ferrous ion is (1.05-1.25):(2-4):

1.

16. The method for preparing the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 15, characterized in that: The temperature during the treatment process is 25~50℃; The processing time is 15~120min.

17. The method for preparing the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 7, characterized in that: The surfactant is an anionic surfactant.

18. The method for preparing the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 17, characterized in that: The surfactant is at least one of sodium dodecylbenzene sulfonate and sodium α-olefin sulfonate.

19. The method for preparing the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 7, characterized in that: The mass ratio of iron phosphate, graphitized carbon and surfactant is (90~100):(7~10):

1.

20. The method for preparing the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 7, characterized in that: The first stage of calcination is carried out under a protective atmosphere.

21. The method for preparing the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 20, characterized in that: The protective atmosphere is nitrogen or an inert gas.

22. The method for preparing the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 20, characterized in that: The temperature of the first calcination process is 300-400°C.

23. The method for preparing the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 20, characterized in that: The first roasting time is 3~5h.

24. The method for preparing the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 7, characterized in that: The amorphous carbon source is at least one of glucose, ascorbic acid and sucrose.

25. The method for preparing the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 7, characterized in that: The sodium source is a component that can provide the Na element.

26. The method for preparing the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 25, characterized in that: The sodium source is at least one of sodium carbonate, sodium bicarbonate, sodium acetate, sodium dihydrogen phosphate and disodium hydrogen phosphate.

27. The method for preparing the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 7, characterized in that: The fluorine source is a component that can provide a fluorine source.

28. The method for preparing the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 27, characterized in that: The fluorine source is at least one of sodium fluoride, ammonium fluoride and hydrogen fluoride.

29. The method for preparing the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 7, characterized in that: The iron phosphate@graphitized carbon precursor, the sodium source and the fluorine source are mixed in a molar ratio of iron phosphate:F:Na of 1~1.2:1~1.3:1~1.

1.

30. The method for preparing the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 7, characterized in that: The mass ratio of the amorphous carbon source to the iron phosphate@graphitized carbon precursor is 3-10wt.%.

31. The method for preparing the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 7, characterized in that: The second stage of calcination is carried out under a protective atmosphere.

32. The method for preparing the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 31, characterized in that: The protective atmosphere is nitrogen or an inert gas.

33. The method for preparing the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 7, characterized in that: The temperature of the second calcination process is 600-650°C.

34. The method for preparing the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to claim 7, characterized in that: The second roasting time is 6~10h.

35. Use of the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material according to any one of claims 1 to 6 or the sodium ferrous fluorophosphate-graphitized carbon@amorphous carbon composite positive electrode material prepared by the preparation method according to any one of claims 7 to 34, characterized in that: Used to prepare sodium ion batteries.

36. The use according to claim 35, characterized in that It is used as a positive electrode active material to prepare the positive electrode of a sodium ion battery.